A Self‐Assembling Tripeptide‐Based Fluorescence Bio‐Nanosensor. Issue 11 (21st September 2020) - Miao, Pandeng; Liu, Zhongdong; Liang, Man; Guo, Jun; Wang, Tegexibaiyin; Wang, Liping; Zhang, Feng
Abstract: A de novo tripeptide, YFF, can self‐assemble into fluorescent nanostructures under ultraviolet irradiation, and their fluorescence can be selectively quenched by copper ions. Copper ions can co‐assemble with YFF NPs into hierarchical nanostructures, and the quenched fluorescence can recover again with the addition of pyrophosphate (diphosphate, PPi), which is due to the robust interaction between copper ions and PPi. Based on this principle, a simple and cost‐effective alkaline phosphatase (ALP) biosensor has been built up by making use of the specific dephosphorylation of ALP to PPi, in which the coordinated copper ions can reversibly bind to PPi, thus quench and recover the fluorescence of tripeptide nanostructures. The fluorescence intensity correlated well to the concentration of Cu 2+ (2–100 μM), PPi (0–500 μM) and ALP (0–500 U/L) i, respectively, and the corresponding limits of detection (LOD) are 1.29 μM, 0.77 μM and 1.84 U/L, respectively. The designed tripeptide‐based nanosensor also exhibits biocompatible, robust sensing performance in serum, indicating its great potential application for clinical diagnosis. Abstract : A biocompatible, simple and cost‐effective tripeptide‐based nanosensor is built for sensing copper ions with high selectivity, which also exhibits excellent assay performance in the evaluation of pyrophosphate and alkaline phosphatase in serologic tests.